Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/cvde.200506380
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Flame‐Made Zirconia‐Based Mixed Oxides

Abstract: The thermal stability of pure and doped zirconia fabricated by flame spray pyrolysis (FSP) is studied by calcination at various temperatures and residence times. Powders are analyzed by X-ray diffraction (XRD), nitrogen adsorption (Brunauer-Emmett-Teller), energy-dispersive X-ray spectroscopy (EDX), and transmission electron microscopy (TEM). The metastable tetragonal structure of flame-made ZrO 2 transformed to the monoclinic phase after sintering. Doping zirconia with yttria, ceria, lanthanum oxide, alumina,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The grain sizes of 4YSZ and 8YSZ calculated by the Scherrer equation were found to be about 21 nm, irrespective of the amount of yttria doping. This result is consistent with results reported by Jossen et al 44 The average particle sizes of 4YSZ and 8YSZ examined using TEM was about 27 nm with a size range from 10 to 50 nm, as shown in Fig. 8, based on the measurement of a rather limited number of particles.…”
Section: Resultssupporting
confidence: 93%
“…The grain sizes of 4YSZ and 8YSZ calculated by the Scherrer equation were found to be about 21 nm, irrespective of the amount of yttria doping. This result is consistent with results reported by Jossen et al 44 The average particle sizes of 4YSZ and 8YSZ examined using TEM was about 27 nm with a size range from 10 to 50 nm, as shown in Fig. 8, based on the measurement of a rather limited number of particles.…”
Section: Resultssupporting
confidence: 93%
“…Figure shows PXRD patterns of CuO/ZrO 2 prepared at P (the precursor feed rate) = 1–10 mL min −1 and pure‐ZrO 2 prepared at P = 2 mL min −1 (FSP‐ZrO 2 ) with NiO powder as an internal standard. Regardless of the Cu loading and the precursor feed rate, the dominant phase of ZrO 2 is tetragonal (t‐ZrO 2 ), which is consistent with other FSP‐made ZrO 2 . In our FSP‐made ZrO 2 , monoclinic ZrO 2 was not formed unlike in the other case .…”
Section: Resultssupporting
confidence: 86%
“…The crystallite size of t‐ZrO 2 decreased from 6.9 to 2.6 nm by decreasing P from 10 to 1 mL min −1 . It was reported that the crystallite size of FSP‐made particles is normally comparable with their primary particle size as they are formed in a high temperature flame (e.g., ZrO 2 , TiO 2 ). Next, the content of t‐ZrO 2 was evaluated from the peak intensity of the above PXRD patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies were focused on zirconia stabilization by different kinds of additives, such cations with lower valence than Zr 4+ as Al 3+ , Y 3+ , Ca 2+ , even oxides such as CeO 2 , SiO 2 , TiO 2 whose cations have the same valence with that of the hostage have been introduced into the lattice of ZrO 2 to form heat standing materials [13][14][15][16][17][18]. Among these additives, yttria (Y 2 O 3 ) was an effective stabilizer and was most widely used.…”
Section: Introductionmentioning
confidence: 99%